1994
DOI: 10.1002/ar.1092400109
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of immobilin in the rat epididymis

Abstract: The results taken together suggest that there are stimulatory and inhibitory luminal testicular factors involved in the regional development of immobilin secretion in the epididymis. There are also immobilin secreting regions in the epididymis, whose secretory development is independent of luminal testicular factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The possibility that circulating androgens regulate the expression of SGP-2 in the distal initial segment and caput can probably be excluded because Cyr and Robaire (1992) demonstrated in adult rats that neither orchidectomy nor testosterone replacement had any effect on SGP-2 mRNA concentrations in these regions. Although a similar shift in expression to the proximal part of the epididymis is observed for SGP-2 and immobilin (Hermo et al, 1994) early in postnatal development, our ligation results indicate that the factors regulating the production of these two proteins at least in the caput epididymidis differ. Ligation represses immobilin expression in the caput epididymidis (Hermo et al, 1994) but has no effect on SGP-2 expression.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…The possibility that circulating androgens regulate the expression of SGP-2 in the distal initial segment and caput can probably be excluded because Cyr and Robaire (1992) demonstrated in adult rats that neither orchidectomy nor testosterone replacement had any effect on SGP-2 mRNA concentrations in these regions. Although a similar shift in expression to the proximal part of the epididymis is observed for SGP-2 and immobilin (Hermo et al, 1994) early in postnatal development, our ligation results indicate that the factors regulating the production of these two proteins at least in the caput epididymidis differ. Ligation represses immobilin expression in the caput epididymidis (Hermo et al, 1994) but has no effect on SGP-2 expression.…”
Section: Discussionsupporting
confidence: 56%
“…Although a similar shift in expression to the proximal part of the epididymis is observed for SGP-2 and immobilin (Hermo et al, 1994) early in postnatal development, our ligation results indicate that the factors regulating the production of these two proteins at least in the caput epididymidis differ. Ligation represses immobilin expression in the caput epididymidis (Hermo et al, 1994) but has no effect on SGP-2 expression. Cyr and Robaire (1992) showed that orchidectomy in adult rats resulted in a substantive increase in SGP-2 mRNA concentrations in the corpus and cauda epididymidis and that testosterone replacement caused a dose dependent decrease in SGP-2 mRNA levels.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations